2020
DOI: 10.1021/acsami.9b23546
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition-Assisted Rapid Preparation of Pt Nanocluster/3D Graphene Hybrid Nanozymes with Outstanding Multiple Oxidase-Like Activity for Distinguishing Colorimetric Determination of Dihydroxybenzene Isomers

Abstract: Here, we demonstrate a facile bottom-up strategy to fabricate Pt nanoclusters (Pt NCs) grafted onto three-dimensional graphene foam (3D GF) assisted by cetyltrimethyl ammonium bromide (CTAB) using the electrodeposition method. The homogeneous grafting of Pt NC onto 3D GF is due to the formation of hemimicelles above some CTAB concentration. With the unique nanocluster structure and the high content of Pt0, the Pt NC/3D GF nanohybrid exhibits extremely high activity and shows higher reusability and stability. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 59 publications
1
23
0
Order By: Relevance
“…According to the previous research studies, the mechanism of peroxidase-like activity of nanoflowers could be attributed to the possibility that the nanoflowers promote electron transfer among H 2 O 2 and TMB (eq 5). 46 These results show that when the concentrations of nanoflowers increases, the adsorption intensity is also increased (Figure 6b). Antimicrobial Activity.…”
Section: K Ksmentioning
confidence: 75%
See 1 more Smart Citation
“…According to the previous research studies, the mechanism of peroxidase-like activity of nanoflowers could be attributed to the possibility that the nanoflowers promote electron transfer among H 2 O 2 and TMB (eq 5). 46 These results show that when the concentrations of nanoflowers increases, the adsorption intensity is also increased (Figure 6b). Antimicrobial Activity.…”
Section: K Ksmentioning
confidence: 75%
“…According to the previous research studies, the mechanism of peroxidase-like activity of nanoflowers could be attributed to the possibility that the nanoflowers promote electron transfer among H 2 O 2 and TMB (eq ). Huang et al investigated the peroxidase-like activity of the BSA Cu 3 (PO 4 ) 2 ·3H 2 O nanoflower and confirmed that the peroxidase-like activity was derived from the Cu 3 (PO 4 ) 2 ·3H 2 O crystal, whereas the BSA was used as an organic component to cause nucleation of Cu 3 (PO 4 ) 2 ·3H 2 O nanopetals. They also verified that the peroxidase-like activity was not due to free copper ion leaching during the reaction and relied on the nanoflower structure.…”
Section: Resultsmentioning
confidence: 99%
“…based carbon nanozymes has been reported by many groups and utilized further for detection, sensing, environmental application, etc. 89,149,150 The electrochemical sensing and The synergy between Pt NC and graphene foam provides the higher catalytic sites for the diffusion of substrates and accelerated electron transfer for redox reactions. This nanozyme shows excellent selectivity and high sensitivity for the catechol oxidation confirmed by mixing different phenols and ions into the solution.…”
Section: -D Nano-carbon Nanozymesmentioning
confidence: 99%
“…This nanozyme shows excellent selectivity and high sensitivity for the catechol oxidation confirmed by mixing different phenols and ions into the solution. 152 A simple self-assembly-based fabrication of the 3D hydrogel using GO, poly(vinyl alcohol) (PVA) molecules, and G-quartet/ hemin (G4/H) motifs was reported by Zhang et al as an electrochemical sensor for the detection of H 2 O 2 to mimic peroxidase-like activity. 153 The GO/PVA/G4/H hydrogel was synthesized via cation-templated self-assembly, as shown in Fig.…”
Section: -D Nano-carbon Nanozymesmentioning
confidence: 99%
“…How to design and construct a favoring composition between MIL-100­(Fe) and GO? As a seamlessly connected porous carbon network, three-dimensional graphene (3DG) is an ideal substrate to accommodate catalysts. More importantly, 3DG can avoid a loss of active sites and break the continuous pathway for electron/phonon transports from the agglomeration of 2D graphene sheets. , Up to date, many 3DG based-nanocomposites, for example, ZnFe 2 O 4 /ZnO/GO foam, Fe 3 O 4 NP-loaded 3DG, , Pt nanocluster/3DG, and 3DG@WO 3 , have been successfully fabricated and exhibited excellent catalytic activities. Considering the above facts, 3DG was chosen to combine with MIL-100­(Fe) based on the following reasons.…”
Section: Introductionmentioning
confidence: 99%